UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII1 MTsN MUARA FAJAR MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN THINK PAIR SQUARE - Marlinda, Weni; Yuanita, Putri; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research is aimed at improving learning process and improving mathematics learning outcomes by implementing Cooperative Learning with Think Pair Square Approach. The research subjects are 24 heterogenous academic ability level students of the VIII1 class students at MTsN Muara Fajar in academic year of 2016/2017. The research consisted of two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the increasing number of students passing Minimum Completeness Criteria (MCC) in daily test I and daily test II. The research shows that teachers and students’ activities were conducted well as planned. Most of the students participated actively in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Therefore, it can be said that improvement of learning process took place in every meeting. Furthermore, the number of students passing the MCC on base score, daily test I (first cycle), daily test II (second cycle) were respectively 6 students (25%), 7 students (29,2%), dan 12 students (50%). The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increase. Finally, the research also shows that cooperative learning with Think Pair Square approach can improve mathematic learning process and learning outcomes of VIII1 class students at MTsN Muara Fajar.Key Words: Math Learning Outcomes, Cooperative Learning with Think Pair Square Approach, Classroom Action Research.